Interface Design of Integrated Infectious Disease Screening Information System in the Teaching Factory for Health Innovation (V-Kes) - Sabran Sabran; Dony Setiawan HP; Mochammad Choirur Roziqin; Khomsatun Ni’mah (P3M Politeknik Negeri Jember, 2026)
Communicable diseases such as Tuberculosis (TB), Dengue Hemorrhagic Fever (DHF), and HIV/AIDS remain major public health challenges in Indonesia, including Jember Regency. Data from the Central Bureau of Statistics and the Ministry of Health indicates an increasing trend in these diseases, emphasizing the importance of early detection through screening as a strategy to reduce transmission and mortality rates. This study creates an interface design that aims to create an infectious disease screening information system based on Artificial Intelligence (AI) that is not yet available in the Teaching Factory for Health Innovation (V-Kes) using the Rapid Application Development (RAD) approach. RAD was chosen because it allows rapid system development through continuous iterations and active user involvement. The research involves a multidisciplinary team from the fields of health, information technology, and management, while V-Kes functions as both an innovation laboratory and a real-world practice setting that integrates digital technology into community-based health services. The expected outputs of this research include scientific publications at national and international conferences, scientific posters, copyright registration of the information system, and a comprehensive final report. This interface design will later enable the developed system to accelerate the detection of infectious diseases, increase service efficiency, and enrich students' learning experiences through the Teaching Factory 4.0 concept. Moreover, this study contributes to strengthening local digital health systems and provides a replicable model for health technology development in other educational institutions.